Analisis Daya Saing Komoditas Vanili Indonesia di Pasar Internasional - Anggraini Susanti; Rasidin Karo Karo Sitepu; Galang Erlangga; Enjelina Damayanti; Safira Kencana Putri; Aldivo Anugraha (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Indonesia is a country that has a good climate for the growth of agricultural plants such as spices. One of the spices, namely vanilla, is a plant that can grow in tropical climates. Vanilla is a spice that is in great demand on the international market considering its benefits in the food, pharmaceutical and cosmetics industries. The target market for vanilla exports in Indonesia is developed countries. This research aims to analyze the competitiveness of Indonesian vanilla exports in the international market, using descriptive statistical analysis methods, Revealed Comparative Advantage (RCA), and Export Product Dynamics (EPD). The data used is secondary data for the 2018-2022 period. The results of the analysis show that the average RCA value is more than one, which means that Indonesian vanilla has strong competitiveness and the EPD analysis shows that the competitiveness of Indonesian vanilla is fluctuating. The results of the analysis show that Indonesia has strong comparative competitiveness of vanilla in destination countries by continuing to increase production levels and maintaining good quality so that it can continue to compete in the international market.